Aggreate Planning Strategies at CV Saswco Perdana - Cashiwan, Cashiwan; Yudoko, Gatot (Journal of Business and Management, 2016)
Abstract. CV Saswco Perdana is a company engaged in clothing industry that located in Gedebage, Bandung. CV Saswco Perdana is a company with medium-large industrial scale. The current condition of the company, they manufactured product in based on order.Based on interview with General Manager of CV Saswco Perdana. Currently the company has 50 employee that work in production division with total capacity can reach 2.500 dozens per month. Otherwise, based on previous data the average demand for 2014 is 730,76 dozens per month and for 2015 the average of demand is 596,94 dozens per month. According to those situation, there is a high level of idle workers that can be occur. So, the company needs to adjusting their workers in order to optimizing their resources and minimizing the total cost. And one of the operations managementâ€™s tool that company can use is aggreate planning strategy. Because by using aggregate planning the company can determines the ideal levels of capacity, production, subcontracting, inventory, stockouts, and even pricing over a specified time horizon (for this research, the time horizon is among 12 months). The research aimed to know the best of aggregate planning strategy that can be implemented by CV Saswco Perdana in order to fulfill the forecasted demand in period 2016 from 5 alternative aggregate planning strategies that conducted in this research, which are: pure chase strategy, pure level strategy, overtime strategy, optimization using linear programming, and mix strategy by varying workforce and overtime, by minimizing unmeet demand and the low cost as key performance. The methodology used is quantitative method. Primary data are collected from interview with Operations Director and General Manager at CV Saswco Perdana. And secondary data is collected from companyâ€™s documents record. Based on all strategies that conducted, the workforce needed is less than 50 workers. Thus, the company needs to adjust their workforce by laying off some workers in order to maximize the resources. The strategy that has the lowest cost is optimization strategy using linear programming with estimation total full costs is Rp.2.407.306.752 and incremental cost is Rp.64.524.912. But, the current work-hour in CV Saswco Perdana is violate the existing of regulations. Especially â€œpasal 77 and pasal 78 UU no. 13 tahun 2003â€ about work-hour and overtime of labor. According to those situation, the author providing the alternative optimization strategy using linear programming with changing the variable of work-hour and overtime related to the regulations as a recommendation. The total cost for alternative optimization using linear programming is Rp.2.610.594.007 and the total incremental cost is Rp.69.464.160.Â Keywords: Demand, Forecast Demand, Optimization Resources, Aggregate Planning.